Phobia Impacts on Adolescents' Psychological Security: A Psychoanalytic Approach: Dampak Fobia terhadap Keamanan Psikologis Remaja: Pendekatan Psikoanalitik - Abdullayeva Muslima (Universitas Muhammadiyah Sidoarjo, 2023)
This research employs a psychoanalytic approach to investigate the effects of phobias on the psychological security of adolescents and the implications for their socio-educational development. The study postulates that phobias result in emotional discomfort and dissatisfaction, thereby weakening individuals' volitional sphere and impairing decision-making capabilities. Data collected were empirically analyzed to discern the balance between self-emotional assessment and psychological protection opportunities during adolescence. The results indicate that phobias, among other effects, reduce environmental tolerance, hinder self-control and personal belief in one's strengths, impede resistance to internal and external influences, decrease self-satisfaction, disrupt communicative skills, and negatively affect the mental state. These impacts collectively lead to a significant drop in the efficiency of the activities a person engages in. Consequently, the study underscores the importance of proper educational interventions from school administrators, teachers, psychologists, and parents to ensure the psychological well-being of adolescents. This approach promises to enhance their resilience and psychological security, enabling their optimal participation in socio-economic activities. Highlights: Phobias significantly affect the psychological security of adolescents, impairing their decision-making capabilities and reducing their overall effectiveness in activities. A psychoanalytic approach provides insights into the balance between self-emotional assessment and psychological protection opportunities during adolescence. Educational interventions from stakeholders (school administrators, teachers, psychologists, parents) are critical in managing phobias among adolescents, promoting psychological well-being, and fostering socio-economic participation. Keywords: Phobias, Adolescents, Psychological Security, Psychoanalytic Approach, Emotional Discomfort